2023
DOI: 10.1182/bloodadvances.2022009652
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the value of mono- vs coculture for high-throughput compound screening in hematological malignancies

Abstract: Large-scale compound screens are a powerful model system for understanding variability of treatment response and for discovering druggable tumor vulnerabilities of hematological malignancies. However, as mostly performed in a monoculture of tumor cells, these assays disregard modulatory effects of the in vivo microenvironment. It is an open question whether and to what extent coculture with bone marrow stromal cells could improve the biological relevance of drug testing assays over monoculture. Here, we establ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Applying relevant cell types and perturbations in morphological profiling assay is essential, but not sufficient to guarantee translatability [ 1 ]. Recent efforts have been made to apply increasingly multiplex biological model systems for image-based profiling, such as cocultured 2D cell lines [ 151 ] and 3D organoids [ 152 , 153 ]. However, on the computational side, most approaches have been built upon Cell Painting assay images from mono-cultured 2D cells.…”
Section: Challenges and Outlookmentioning
confidence: 99%
“…Applying relevant cell types and perturbations in morphological profiling assay is essential, but not sufficient to guarantee translatability [ 1 ]. Recent efforts have been made to apply increasingly multiplex biological model systems for image-based profiling, such as cocultured 2D cell lines [ 151 ] and 3D organoids [ 152 , 153 ]. However, on the computational side, most approaches have been built upon Cell Painting assay images from mono-cultured 2D cells.…”
Section: Challenges and Outlookmentioning
confidence: 99%
“…We evaluated the linear correlations between CD28 and CD38 target expression, as well as the linear correlations of drug response and TC activation and the correlations between target expression and MM cell death, using the Pearson correlation coefficient. The Pearson correlation measures the strength and direction of the linear relationship between two variables, allowing for comparison of the degree of linear association between drug response profiles across different cell lines and patients [40]. Statistical details have been provided in the figures and figure legends.…”
Section: Quantification and Statistical Analysismentioning
confidence: 99%
“…Nonetheless, while recent work has shown that in vitro drug treatment phenotypes can depend on relative oxygen tension 22 , the presence of stromal cells 23,24 , and culture in 3D models [25][26][27][28] , there has been considerably less attention on the influence of medium composition 29 -arguably the most flexible component of the in vitro environment.…”
Section: Introductionmentioning
confidence: 99%